2006
DOI: 10.1158/1078-0432.ccr-06-1037
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin Preferentially Binds Mitochondrial DNA and Voltage-Dependent Anion Channel Protein in the Mitochondrial Membrane of Head and Neck Squamous Cell Carcinoma: Possible Role in Apoptosis

Abstract: Purpose: Cisplatin adducts to nuclear DNA (nDNA) are felt to be the molecular lesions that trigger apoptosis, but the mechanism linking nDNA adduct formation and cell death is unclear. Some literature in the last decade has suggested a possible direct effect of cisplatin on mitochondria independent of nDNA interaction. In this study, we define separately the sequelae of cisplatin interactions with nDNA and with mitochondria in head and neck squamous cell carcinoma (HNSCC) cell lines. Experimental Design: Cispl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
189
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(199 citation statements)
references
References 56 publications
7
189
0
3
Order By: Relevance
“…Both CDDP and OXP are mostly considered as DNA-damaging agents. However, both CDDP and OXP can induce apoptosis-associated changes in cytoplasts (Gourdier et al, 2004;Yang et al, 2006), that is, cells that have been enucleated, meaning that both of these agents have poorly characterized cytoplasmic targets, which must be at least in part agent-specific. We surmise that, in contrast to OXP, CDDP fails to affect the conformation of proteins that would cause an unfolded protein response in the ER, although the molecular details of this differential effect remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Both CDDP and OXP are mostly considered as DNA-damaging agents. However, both CDDP and OXP can induce apoptosis-associated changes in cytoplasts (Gourdier et al, 2004;Yang et al, 2006), that is, cells that have been enucleated, meaning that both of these agents have poorly characterized cytoplasmic targets, which must be at least in part agent-specific. We surmise that, in contrast to OXP, CDDP fails to affect the conformation of proteins that would cause an unfolded protein response in the ER, although the molecular details of this differential effect remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that cisplatin-induced apoptosis can be initiated through both intrinsic and extrinsic pathways. Cisplatin induces rapid dosedependent release of cytochrome c from mitochondria to cytosol (58,59). Cytochrome c subsequently activates the caspase cascade, eventually leading to apoptotic cell death (60).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to this, cisplatin has been shown to bind mitochondrial DNA as well as the voltage-dependent anion channel (VDAC) (Yang et al, 2006), a mitochondrial protein with vital and lethal functions (Kroemer et al, 2007). Notably, VDAC-depleted cancer cells are highly resistant to CDDP treatment (Tajeddine et al, 2008), yet it is not clear whether this constitutes an example of ontarget resistance or whether in this context VDAC simply transduces upstream proapoptotic signals (and hence would be involved in a post-target resistance mechanism).…”
Section: Mlh1mentioning
confidence: 99%